A Rare Cause of Cyanosis: Hepatopulmonary Syndrome Caused by Congenital Extrahepatic Portosystemic Shunt - Xue-Yan Ding; Feng Chen; Xian-Xian Zhao; Hong Wu; Shao-Ping Chen; Yong-Wen Qin (Case Reports in Vascular Medicine, 2011)
A 19-year-old male patient presented cyanosis and dyspnoea because of the presence of multiple pulmonary arteriovenous fistulas resulting in oxygen desaturation. The CTA revealed that intestinal and splenic venous blood bypasses the liver and drains into the inferior vena cava. This is the first reported case of hepatopulmonary syndrome caused by congenital extrahepatic portosystemic shunt in which intestinal and splenic venous blood bypasses the liver and drains into the inferior vena cava.